2012
DOI: 10.1155/2012/987471
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus as a Trigger of Autoimmune Liver Diseases

Abstract: The pathogenesis of autoimmune diseases includes a combination of genetic factors and environmental exposures including infectious agents. Infectious triggers are commonly indicated as being involved in the induction of autoimmune disease, with Epstein-Barr virus (EBV) being implicated in several autoimmune disorders. EBV is appealing in the pathogenesis of autoimmune disease, due to its high prevalence worldwide, its persistency throughout life in the host's B lymphocytes, and its ability to alter the host's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 149 publications
(210 reference statements)
1
32
0
2
Order By: Relevance
“…Admittedly, many case studies demonstrate a strict temporal relation between pathogen infection and the development of acceleration of AIH. In particular, HAV, HCV, and EBV have been discussed to play a role in AIH [65,113]. However, in contrast to other autoimmune diseases (see reviews in this special issue of IRI) the data for an involvement of pathogens are rare and firm evidence from large cohorts is missing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Admittedly, many case studies demonstrate a strict temporal relation between pathogen infection and the development of acceleration of AIH. In particular, HAV, HCV, and EBV have been discussed to play a role in AIH [65,113]. However, in contrast to other autoimmune diseases (see reviews in this special issue of IRI) the data for an involvement of pathogens are rare and firm evidence from large cohorts is missing.…”
Section: Resultsmentioning
confidence: 99%
“…Another prominent candidate is Epstein-Barr virus (EBV), a pathogen that has been very frequently associated with the development of several autoimmune diseases, including systemic lupus erythematosus (SLE), multiple sclerosis (MS), autoimmune forms of thyroiditis (Grave's disease and Hashimoto's disease), rheumatoid arthritis (RA), inflammatory bowel disease (IBD), type 1 diabetes (T1D), Sjögren's syndrome (SjS), and myasthenia gravis (MG) as well as autoimmune liver diseases [65]. In the present review, we will focus on the role of EBV in AIH, and refer to a recent review by Rigopoulpu et al for an excellent overview on the role of EBV in autoimmune liver diseases, such as PBC and PSC [65].…”
Section: Epstein-barr Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…HEV is a leading cause of acute hepatitis in developing countries and an emerging causative agent of acute and chronic hepatitis in Europe (4)(5)(6). A recent study from the Robert Koch Institute found an anti-HEV prevalence of 16.8% in the adult population in Germany (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic EBV infection is a possible triggering factor for not only IBD but for other autoimmune diseases including autoimmune hepatitis, systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis. 2,3,18 The pathogenesis of autoimmune disease related to EBV infection is not clear. Autoimmunity may develop because of molecular mimicry, which is defined as immunological cross-reactivity between EBV and self-antigens.…”
Section: 오승현 등 Ebv로 인한 간염 후 발생한 궤양성 대장염mentioning
confidence: 99%